Processos difusionais, cristalização e escoamento viscoso em dissilicato de bário vítreo - Rodrigues, Alisson Mendes (2014)
In this work, we analysed if the viscous flow successfully describes the transport of crystal nucleation and crystal growth structural units that occur at the liquid/crystal interface. In order to do this, we calculated the diffusion coefficient which controls the viscous flow, Dη, from experimental viscosity data using the Eyring equation and compared with diffusion coefficients that control the phenomena of crystal nucleation and growth (Dτ and DU), calculated from experimental measurements of specific heat, viscosity, crystal nucleation and growth. The analysis showed that the diffusion coefficient Dη satisfactorily describes the dependence of the diffusion coefficients Dτ and DU at high temperatures. However, for temperatures below 1.03Tg and 1.19Tg for crystal nucleation and growth, respectively, we observed a phenomenon called decoupling (or breakdown) that is the inability to use Dη. to describe Dτ and DU with temperature. This phenomenon was observed for other glassy materials and the values found in this study are consistent with the literature. All the experimental measurements performed in this study were obtained from the same batch of a stoichiometric glass with composition 33.3BaO.66.7SiO2-mol% where the chemical homogeneity was assessed (and deemed satisfactory) from a probability method using Poisson`s distribution. This work also proposed a new method to quantitatively measure the heating rate that should be used in a DSC furnace to prevent the formation of new nuclei. We then applied this method to the glass 33.3 BaO.66.7SiO2 and obtained the value of 25 °C/min. This value is in reasonable agreement with predictions from the literature that suggest a heating rate equal to 20 °C/min is sufficient to prevent the formation of new nuclei silicate glasses.